La escuela histórico-cultural: una mirada actual - Bell Rodríguez, Rafael (2016)
In the pursuit of finding answers, both from the theoretical and methodological point of view in order to promote a raise in the quality of education, an aspect calling attention is the importance of ideas derived from different schools and psychological approaches. One of the most outstanding approaches is the one based on historical- cultural school of LS Vygotsky and his followers.Having this as a reference point, this article outlines some of the main principles of the current historical- cultural school. At the same time it highlights some great features of the developer school as a conception with one of the highest number of potentialities in order to contribute to the quality step up teaching needs in these days.